Role of Hepatocyte Nuclear Factor 4 Alpha in Liver Cancer - Kotulkar, Manasi; Paine-Cabrera, Diego; Apte, Udayan (Seminars in Liver Disease, 2024)
Liver cancer is the sixth most common cancer and the fourth leading cause of cancer-related deaths worldwide. Hepatocellular carcinoma (HCC) is the most prevalent primary liver cancer and the incidence of HCC is on the rise. Liver cancers in general and HCC in particular do not respond to chemotherapy. Radiological ablation, surgical resection, and liver transplantation are the only medical therapies currently available. Hepatocyte nuclear factor 4 α (HNF4α) is an orphan nuclear receptor expressed only in hepatocytes in the liver. HNF4α is considered the master regulator of hepatic differentiation because it regulates a significant number of genes involved in various liver-specific functions. In addition to maintaining hepatic differentiation, HNF4α also acts as a tumor suppressor by inhibiting hepatocyte proliferation by suppressing the expression of promitogenic genes and inhibiting epithelial to mesenchymal transition in hepatocytes. Loss of HNF4α expression and function is associated with rapid progression of chronic liver diseases that ultimately lead to liver cirrhosis and HCC, including metabolism-associated steatohepatitis, alcohol-associated liver disease, and hepatitis virus infection. This review summarizes the role of HNF4α in liver cancer pathogenesis and highlights its potential as a potential therapeutic target for HCC.
Keywords: liver cancer; HCC; HNF4α; therapeutic target